Pluralidade na cobertura do Jornal Nacional sobre os preparativos para a Copa do Mundo 2014 : avaliação da conformidade do conteúdo jornalístico com as garantias do documento editorial das Organizações Globo - Tavares, Bruno da Silva (2014)
This research aims to assess the degree of compliance of |Jornal Nacional| TV News, with the requirements of plurality ensured in the document |Editorial Principles of Globo Organizations|, on the cover of the preparations for the FIFA World Cup and Confederations Cup events. The work is divided into two parts: In the first, it is discussed the concept of plurality in journalism; how this value is related to the pluralist model of democratic theories; in which political circumstances this requirement of the journalistic activity helps to legitimize the journalism as a mediation forum of antagonistics and various positions. In parallel, we identified the editorial guidance document of |Rede Globo| Network as a tool for accountability processes, which enables the monitoring of journalistic content on the part of users, in order to check if the company delivers what ensures produce. The oriented devices to charge the journalistic processes for advertising and responsability of those who produce a public service are understood as a way of strengthening the producer-audience relationship, which competes for the extension of the social responsibility´s activity. In the second part, it´s presented the evaluation of plurality, in which was employed a methodology, developed in the framework of |Program of Research on Quality, Innovation and Technology Applied to Journalism| (Qualijor), which evaluated two aspects of the company: the editorial principles document of Globo Organizations; And the coverage of Jornal Nacional| TV News on the preparations of the mentioned events, with regard to compliance with the requirements for a plural coverage: 1) media autonomy in relation to the parties; 2) debate accessibility by agents potentially involved and 3) balance in the involved participation. The |Rede Globo| Network, as a FIFA´s partner and promoter of the World Cup, hosts the debate about the event in its TV News, but it is also interested party, setting up as well, a situation of conflict of interest that puts into question the basic condition for promotion of a plural coverage, contradicting guarantees provided in its document. In this scenario, this search looks for signs of asymmetry between what is guaranteed and what, in fact, is offered by the journalism of the broadcaster in relation to the plurality; suggesting as well, the increase in the debate on supervision mechanisms of journalistic content, in reason of the quality desired by its producers.